Fatal Road Traffic Accidents in Karachi (Medical Forum Monthly, 2024)
Objective: Fatalities due to road traffic accidents are a major cause of mortality all over the world. The aim of our study is to look at socio-demographic profile of such cases in order to find some remedial measures to minimize the brunt.Study Design: Retrospective / observational study.Place and Duration of Study: This study was conducted at the Emergency Department, Sir Syed Hospital, Qayyumabad, Karachi from January to June, 2013. Materials and Methods: Study was based upon 56 victims of RTA. It includes all those who died during treatment or found dead on arrival in the emergency department. The demographic data of these cases was recorded. Results: Males victims were 71% & maximum number of victims (37.5%) was in age group 30-39 years. Most of the accidents (38%) took place between 1200hrs & 1800hrs. Most of the injuries were found on the head (66%) and then chest 14%, lower extremities 21%, upper extremities 19%. The most common external injuries were abrasions, bruises and lacerations. Skull was the most common bone to be fractured (44%). The head injury constituted major cause of death (53%) followed by hemorrhagic shock (35%). Pedestrians and two wheeler riders were mostly affected individuals followed by cyclists, drivers of three wheeler, light and heavy motor vehicles.Conclusion: The incidence of traffic accidents is at rampant. The accidents risks can be minimized by enhancement of road visibility, good traffic control with properly working road traffic signals. Fatalities of Traffic accidents victims can be reduced by providing good pre-hospital care, establishment of well equipped emergency trauma centres in all big hospitals.